Ukuran Perusahaan, Hutang, dan Profitabilitas dalam pendekatan klasik pada Perusahaan non-keuangan di Indonesia - Irene Natalia (Jurnal Bisnis dan Akuntansi, 2021)
Information on company profitability is needed by investors and creditors. This study aims to provide empirical evidences that companies that have less debt and are larger in size have higher profitability. The dependent variable used is profitability. The independent variables used are company size (assets and receivables) and debt. The relationship between firm size and profitability is built on technological theory (economies of scale), agency costs, and competence theory. The relationship between debt and profitability is built on the pecking order theory (choice of funding sources) and the control hypothesis (benefits of using debt). The research population used is all non-financial companies listed on the Indonesia Stock Exchange from 2017 to 2019 using the purposive sampling method. The collected panel data were tested using the regression method with the type of random effect model. Data testing was carried out using the Gretl application with a random effect model estimated by the Nerlove method. Firm size (receivables) and debt affect profitability. Effective use of assets in company operations supports increased profitability. The use of debt as a control tool needs to be applied at the right time. Alignment of the value of receivables and the value of payables need to be done with the value of other assets.